Integrative Transcriptomics and Proteomics Analysis Provide a Deep Insight Into Bovine Viral Diarrhea Virus-Host Interactions During BVDV Infection - Ma, Yingying; Wang, Li; Jiang, Xiaoxia; Yao, Xin; Huang, Xinning; Zhou, Kun; Yang, Yaqi; Wang, Yixin; Sun, Xiaobo; Guan, Xueting; Xu, Yigang (Frontiers in Immunology, 2022)
Bovine viral diarrhea virus (BVDV) is the causative agent of bovine viral diarrhea-mucosal disease (BVD-MD), an important viral disease in cattle that is responsible for extensive economic losses to the cattle industry worldwide. Currently, several underlying mechanisms involved in viral replication, pathogenesis, and evading host innate immunity of BVDV remain to be elucidated, particularly during the early stage of virus infection. To further explore the mechanisms of BVDV-host interactions, the transcriptomics and proteomics profiles of BVDV-infected MDBK cells were sequenced using RNA-seq and iTRAQ techniques, respectively, and followed by an integrative analysis. Compared with mock-infected MDBK cells, a total of 665 differentially expressed genes (DEGs) (391 down-regulated, 274 up-regulated) and 725 differentially expressed proteins (DEPs) (461 down-regulated, 264 up-regulated) were identified. Among these, several DEGs and DEPs were further verified using quantitative RT-PCR and western blot. Following gene ontology (GO) annotation and KEGG enrichment analysis, we determined that these DEGs and DEPs were significantly enriched in multiple important cellular signaling pathways including NOD-like receptor, Toll-like receptor, TNF, NF-κB, MAPK, cAMP, lysosome, protein processing in endoplasmic reticulum, lipid metabolism, and apoptosis signaling pathways. Significantly, the down-regulated DEGs and DEPs were predominantly associated with apoptosis-regulated elements, inflammatory factors, and antiviral elements that were involved in innate immunity, thus, indicating that BVDV could inhibit apoptosis and the expression of host antiviral genes to facilitate viral replication. Meanwhile, up-regulated DEGs and DEPs were primarily involved in metabolism and autophagy signaling pathways, indicating that BVDV could utilize the host metabolic resources and cell autophagy to promote replication. However, the potential mechanisms underlying BVDV-host interactions required further experimental validation. Our data provide an overview of changes in transcriptomics and proteomics profiles of BVDV-infected MDBK cells, thus, providing an important basis for further exploring the mechanisms of BVDV-host interactions.